Art, War and Counter-Images - Rasmussen, Mikkel Bolt (The Nordic Journal of Aesthetics, 2014)
The article analyses the relatively meager response of artists to the ‘war on terror’ compared to the response of American artists to the war in Vietnam, where artists organized both exhibitions and protests against the war in South East Asia in the late 1960s. This of course has to do with the transformations going in contemporary art and the broader political context characterized by the hegemony of neo-liberalism. The article juxtaposes an installation by the Retort collective with an installation by Alfredo Jaar, analyzing two different ways of confronting the image war of the capitalist state machine with either a heave-handed use of art or a negative representation.